2021
DOI: 10.3390/su13063568
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Responsibility Disclosure, Information Environment and Analysts’ Recommendations: Evidence from Malaysia

Abstract: The purpose of this study was to extend our understanding of how corporate social responsibility (CSR) disclosures impact capital market participants, specifically sell-side analysts. The sample of this study was based on a dataset from a panel of 285 Malaysian firms for the period of 2008–2013 (738 firm-year observations). This study employed ordinary least square regression. This study found that firms with better CSR disclosures are more likely to receive optimistic investment recommendations. Subsample ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 149 publications
4
27
1
1
Order By: Relevance
“…Despite a large body of literature on family businesses, empirical research on familycontrolled firms and CSR is still in its infancy [3]. Ref.…”
Section: The Moderating Roles Of Family Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a large body of literature on family businesses, empirical research on familycontrolled firms and CSR is still in its infancy [3]. Ref.…”
Section: The Moderating Roles Of Family Ownershipmentioning
confidence: 99%
“…In recent years, corporate social responsibility (CSR) has emerged as a critical and enduring topic that has attracted rapidly growing scholarly attention. This explosion reflects increasing awareness among firms of their roles and responsibilities to the community as well as the environment [1][2][3][4][5]. CSR participation by firms has been extensively scrutinized by the media, socially responsible investors, and numerous CSR rating agencies, such as Morgan Stanley Capital International, Sustainalytics, FTSE Russell, Bloomberg, and Thomson Reuters, and any CSR misconducts could have a significant impact on a firm's reputation and its sustainability [6].…”
Section: Introductionmentioning
confidence: 99%
“…The study makes the following contributions. First, most studies that examine the determinants of analysts' stock recommendations have considered various firm-specific factors such as corporate governance strength (Papangkorn et al, 2020;Yu, 2011), corporate social responsibility initiatives (Alazzani et al, 2021;García-Sánchez et al, 2020;Ioannou & Serafeim, 2015;Wan-Hussin et al, 2021), earnings growth and risk (Peasnell et al, 2018), shareholder rights (Autore et al, 2009), equity incentive plans (Liu, 2017), financial restatements (Qasem et al, 2020) and degree of internationalisation (Luo & Zheng, 2018). Our study extends the literature by examining the relationship between institutional investor heterogeneity and sell-side analyst stock recommendation, an area that has so far received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, having many persons sit on the board with various experience and qualifications may enhance their legitimacy. Past studies have demonstrated a strong association between sustainability or environmental practices and board size [31,[52][53][54]. Benomran, et al [52], who studied the effect of board size on corporate social and environmental disclosure in Libya, revealed the positive and significant linkage between the two.…”
Section: Hypothesis 2 (H2mentioning
confidence: 97%